KERAMAHTAMAHAN KOMUNIKASI DALAM ISLAM: STUDI ANALITIK DALAM TAFSIR KONTEMPORER - Abdul Mufid (el-'Umdah, 2020)
This article tries to explain the various levels of friendliness associated with human communication. This study focuses on Qur'anic verses that talk about ethical behavior towards others and analyze the context. The divine message given to the Prophet Muhammad emphasized the importance of friendly relations in every area of ??human life. This hospitality plays a very important role in avoiding misunderstanding and conflict in society. The emergence of tension between individuals in the community has always been the result of verbal violence and negative words that were raised when communicating. This study uses a deductive method by analyzing the views of contemporary scholars in the field of Qur'anic interpretation which interprets verses with a contextual approach. The scope of this study is limited to the analysis of the interpretation of verses relating to ethical relations between individuals, family members, various religious adherents, and government leaders. The significance of this research is to answer the question why humans should benefit from the Qur'an's guidance on communication hospitality to maintain peace and harmonious life.